Two new arthroconidial yeast species from bark and pit mud in China - Hai-Yan Zhu; Yu-Hua Wei; Liang-Chen Guo; Zhang Wen; Shuang Hu; Di-Qiang Wang; Xiao-Long You; En-Di Fan; Shang-Jie Yao; Feng-Yan Bai; Pei-Jie Han (MycoKeys)
A study on yeast species from the genera Geotrichum and Magnusiomyces in southwest and central China was conducted based on morphological and molecular phylogenetic analyses using the ITS region and the D1/D2 domain of the LSU rRNA gene. The research identified two new yeast species: Geotrichum hubeiense and Magnusiomyces pitmudophilus. The study contributed to understanding arthroconidial yeast diversity in fermentation and natural environments and paved the way for future taxonomic and ecological studies. Descriptions, illustrations, and phylogenetic analysis results of the two new taxa are provided.